2019
DOI: 10.1186/s12940-019-0488-0
|View full text |Cite
|
Sign up to set email alerts
|

The USA lags behind other agricultural nations in banning harmful pesticides

Abstract: Background The United States of America (USA), European Union (EU), Brazil and China are four of the largest agricultural producers and users of agricultural pesticides in the world. Comparing the inclination and ability of different regulatory agencies to ban or eliminate pesticides that have the most potential for harm to humans and the environment can provide a glimpse into the effectiveness of each nation’s pesticide regulatory laws and oversight. Methods The approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(141 citation statements)
references
References 30 publications
0
117
0
5
Order By: Relevance
“…A similar comparison result was made in our previous work [38], demonstrating relatively low levels of chlorpyrifos in the dust of U.S. houses compared to our Taiwanese data. As chlorpyrifos and terbufos have been banned for domestic use respectively in the U.S. and in China and European Union [41], exposure to OPs should be of concern in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…A similar comparison result was made in our previous work [38], demonstrating relatively low levels of chlorpyrifos in the dust of U.S. houses compared to our Taiwanese data. As chlorpyrifos and terbufos have been banned for domestic use respectively in the U.S. and in China and European Union [41], exposure to OPs should be of concern in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…There are still many differences among EU, the United States and developing countries, in the use of pesticides . Many pesticides that have been banned or are being phased out in the EU, China and Brazil are still in large use in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…There are still many differences among EU, the United States and developing countries, in the use of pesticides. 65 Many pesticides that have been banned or are being phased out in the EU, China and Brazil are still in large use in the United States. Currently, the strictly EU regulation is the most comprehensive and protective (information available from https://eur-lex.europa.eu/legal-content/EN/TXT/?uri=CELEX: 32009R1107).…”
Section: Discussionmentioning
confidence: 99%
“…For the four pyrethroid insecticides analyzed in this study (bifenthrin, cypermethrin, fenpropathrin, permethrin), the FQPA factor determination is based on a policy document released in July 2019, which stated that "the total FQPA safety factor for pyrethroids can be reduced to 1X for all populations" [29]. For the fungicide metalaxyl, the EPA did not assess a chronic dietary exposure In light of the recent report by Donley on the differences in pesticide oversight in the U.S. and other countries [1], it is notable that the three pesticides with a 10X FQPA safety factor for chronic dietary exposures have use restrictions in the European Union and are classified as "not approved" in the EU pesticide database as of January 2020 [73]. In animal studies, chlorpropham was associated with an increase in Leydig cell tumors in the testes of male rats and the potential for endocrine disruption [74,75].…”
Section: Selection Of Pesticides For the Analysismentioning
confidence: 99%
“…A recent study published in Environmental Health concluded that the U.S. has lagged behind other agricultural nations in banning harmful pesticides and suggested that pesticide bans can catalyze the transition to safer alternatives [1]. A similarly important question is whether, in the current practice of pesticide registrations in the U.S., all measures are taken to protect the public, especially infants and children, from the potentially harmful effects of pesticides.…”
Section: Introductionmentioning
confidence: 99%